Circ_0007534 as new emerging target in cancer: Biological functions and molecular interactions - Liu, Bowen; Dong, Chengbin; Chen, Quan; Fan, Zhenhua; Zhang, Yu; Wu, Yifan; Cui, Ting; Liu, Fuquan (Frontiers in Oncology, 2022)
Circular RNA (circRNAs), an important member of the non-coding RNA (ncRNA) family, are widely expressed in a variety of biological cells. Owing to their stable structures, sequence conservations, and cell- or tissue-specific expressions, these RNA have become a popular subject of scientific research. With the development of sequencing methods, it has been revealed that circRNAs exert their biological function by sponging microRNAs (miRNAs), regulating transcription, or binding to proteins. Humans have historically been significantly impacted by various types of cancer. Studies have shown that circRNAs are abnormally expressed in various cancers and are involved in the occurrence and development of malignant tumors, such as tumor cell proliferation, migration, and invasion. As one of its star molecules, circ_0007534 is upregulated in colorectal, cervical, and pancreatic cancers; is closely related to the occurrence, development, and prognosis of tumors; and is expected to become a novel tumor marker and therapeutic target. This article briefly reviews the expression and mechanism of circ_0007534 in malignant tumors based on the domestic and foreign literature.